Konstruksi Ide Xi Jinping dalam Belt And Road Initiative - Arief Bakhtiar Darmawan; Rahmad Agus Dwianto; Herdho Husna Akmala (Sospol : Jurnal Sosial Politik, 2022)
This paper aims to understand the role of Xi Jinping's ideas and perceptions about China's rise in the Belt and Road Initiative (BRI). It released by Xi Jinping in 2013 as the one of ambitious policy to drive China's rise as the world power. He has a strong position in Chinese politics. In addition to leading the government, Xi is the military's commander-in-chief and has the potential to serve as president for three terms. His thoughts have even entered into the Constitution of the Chinese Communist Party. Xi's accumulation of power began to be juxtaposed with Mao's power who had a sacred position in society. Using constructivist approach, this paper attempts to analyze the role of non-material factor, such as the ideas of leader, in determining the direction of Chinese foreign policy. As the qualitative research, primary data obtained from the analysis of official government documents related to Xi Jinping's speech, the Chinese constitution, BRI, as well as official websites. Meanwhile, mass media news, scientific publications as well as other research reports consider as secondary data. It examines the practice of China's foreign policy is controlled and shaped by Xi Jinping's idea of China's rise. As a result, his ideas have played a role in changing the ways of diplomacy and the use of power that see BRI as China's global strategy, especially in China's relations with the US at the global level and cooperation with Southeast Asian and East Asian countries in order to streamline the BRI project.